Incorporating Agricultural, Socioeconomic, and Political Factors into Conservation Strategies for the Giant Armadillo (Priodontes maximus) in the Cerrado - Bruna Gomes de Oliveira (2023)
Species distribution models are essential for proposing conservation strategies for large mammals. However, anthropogenic factors must be incorporated to enhance the effectiveness of these strategies. In this study we selected the Giant Armadillo (Priodontes maximus) as a target species. We mapped its distribution and analyzed the landscape structure in its potential occurrence area. Simultaneously, we mapped the socioeconomic, agrarian, and public governance dimensions of Cerrado municipalities, which were categorized into groups to assess the local context. Combining these results, we discussed conservation strategies for the species in the local-regional context. For the distribution modeling, 486 independent presence points and 14 predictor variables were utilized, resulting in a model with 695,367 km2 of remaining habitat for the species. It corresponds to 33% of the Cerrado biome, with 7.6% of this area within protected areas or Indigenous Lands. Five anthropic variables were employed to classify the 1,434 municipalities in the study area, resulting in three distinct municipal profile groups. A map and a framework were then generated, combining municipal profile information and the amount of remaining habitat per municipality to guide decision-making on conservation strategies first steps. One group stood out due to the presence of large surplus of remaining native vegetation in both private properties and protected areas, indicating significant conservation opportunities.